2020
DOI: 10.3390/rs12162611
|View full text |Cite|
|
Sign up to set email alerts
|

SAR Sentinel 1 Imaging and Detection of Palaeo-Landscape Features in the Mediterranean Area

Abstract: The use of satellite radar in landscape archaeology offers great potential for manifold applications, such as the detection of ancient landscape features and anthropogenic transformations. Compared to optical data, the use and interpretation of radar imaging for archaeological investigations is more complex, due to many reasons including that: (i) ancient landscape features and anthropogenic transformations provide subtle signals, which are (ii) often covered by noise; and, (iii) only detectable in specific so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 58 publications
0
18
0
5
Order By: Relevance
“…x,y g x,y g m Z (20) where, m is the number of pixels of the target LCB. The LCB edge features that carry the characteristics of human vision were extracted, and the template matching coefficient θLTM was configured.…”
Section: Lcb Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…x,y g x,y g m Z (20) where, m is the number of pixels of the target LCB. The LCB edge features that carry the characteristics of human vision were extracted, and the template matching coefficient θLTM was configured.…”
Section: Lcb Divisionmentioning
confidence: 99%
“…Based on genetic algorithm and quadrature mirror filter, Smutnicki [19] put forward a visual effect optimization method to overcome the low resolution and severe information loss of classical landscape images, and proved that the method can output high resolution images and extract desirable image features. Elfadaly et al [20] combined the histogram equalization with the imaging mechanism into a hybrid strategy: Firstly, the salient areas in each fuzzy landscape image are equalized; the contrast difference vectors of the salient areas are acquired by histogram specification; the difference vectors were optimized to reconstruct an enhanced image.…”
Section: Introductionmentioning
confidence: 99%
“…The reconnaissance of typical archeological marks (such as crop, shadow, and soil/damp marks) using radar is more complex than optical imaging [13]. The discriminability of archeological marks is a complex issue mainly because linked to very subtle and nonpermanent signals [14], [15] only evident in specific surface conditions, (as for example, vegetation type and phenology, moisture content, etc.) that can be captured using a multitemporal data processing [15].…”
Section: Introductionmentioning
confidence: 99%
“…1). For both S-1 and S-2, the processing was addressed to feature enhancement and data reduction to capture archeological features and characterize their spatial and temporal variations in terms of both size and distribution [11], [14]. This was performed using Javascript in GEE to obtain Bands combination, RGB composition, Spectral Signature and Backscattered observation, and PCA [11].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically for heritage management, while earth observation has been well introduced in the literature, the majority of these studies are focused on the exploitation of a limited number of high-resolution optical sensors [ 18 , 19 , 20 , 21 ] with some noticeable exceptions [ 22 , 23 ]. Even fewer studies are found in the literature to be dealing with the use of radar sensors at a medium resolution [ 24 , 25 ]. Indeed, the use of the Copernicus Sentinel-1 radar sensor [ 26 ] is still limited for heritage management applications, with exceptions in the application of interferometric synthetic-aperture radar (In-SAR) analysis [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%